2001
DOI: 10.1152/jappl.2001.91.2.667
|View full text |Cite
|
Sign up to set email alerts
|

An inexpensive meter to measure differences in electrical resistance in the rat vagina during the ovarian cycle

Abstract: The inherent electrical resistance of the rat vaginal wall rises markedly near the beginning of estrus and then falls again to low levels for the remainder of the ovarian cycle. Accordingly, special instruments have been developed to measure such resistances (within seconds) on simply inserting a small probe fitted with a pair of recording electrodes into the vagina (i.e., the MK-10A impedance checker and the EC40 estrus cycle monitor). As described herein, these two instruments are far more convenient for mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…Cycle stages were determined by recording daily electrical impedance readings of the vaginal wall using a commercially available EC40 estrous cycle monitor (Fine Science Tools, Foster City, Calif., USA). The EC40 estrous cycle monitor measures the inherent electrical resistance of the vaginal wall which fluctuates markedly across different phases of the estrous cycle [13]. Vaginal lavage and microscopic determination of vaginal cytology was also used to confirm estrous cycle stage determinations.…”
Section: Methodsmentioning
confidence: 99%
“…Cycle stages were determined by recording daily electrical impedance readings of the vaginal wall using a commercially available EC40 estrous cycle monitor (Fine Science Tools, Foster City, Calif., USA). The EC40 estrous cycle monitor measures the inherent electrical resistance of the vaginal wall which fluctuates markedly across different phases of the estrous cycle [13]. Vaginal lavage and microscopic determination of vaginal cytology was also used to confirm estrous cycle stage determinations.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the estrous stage, the cycle of female Wistar rats (Harlan laboratories, Horst, The Netherlands) was measured daily in the late afternoon with an impedance checker (Impedance Checker MK-10B, Muromachi; see also Ramos et al 2001). When a female reached the estrous stage it was placed together with a Wistar male (Harlan laboratories, Horst, The Netherlands) in Macrolon type 3 cage (42× 26×20 cm) with a wire gauze bottom.…”
Section: Animalsmentioning
confidence: 99%
“…Each rat was lightly restrained, and a probe inserted into the vagina for about 5 s. The probe provides a measure of the resistance of the vaginal mucosa, which is known to increase on the morning of estrus to a value greater than 6000 Ω, relative to a basal value of 2000-3000 Ω on other days of the estrous cycle (Koto et al, 1987a,b;Ramos et al, 2001). Prior studies have confirmed that increased vaginal resistance occurs when the vaginal cell type obtained from swabs is predominantly of the cornified type (Ramos et al, 2001). After each use, the probe was cleaned using distilled water, dried, and then wetted with distilled water prior to the next resistance determination.…”
Section: Female Ratsmentioning
confidence: 99%